Omah Kaktus Interior Design With Biophilic Concept In Bandung: English - Fitri Marati Sholihah; Pandu Purwandaru (TAMA: Journal of Visual Arts, 2025)
Omah Kaktus interior design is an educational facility that provides a facility or place that can accommodate and facilitate cactus cultivation business activities for MSMEs and cactus farmers. Aims as an attractive educational and tourist facility for the community, especially in the city of Bandung. This facility is expected to be an educational facility that is able to accommodate cactus cultivation and management of the benefits of cactus by providing various information, education and recreation for visitors. The formulation of the problem of this design is how the interior design of Omah Katkus can be an economic driver facility for the local community and tourism that is attractive to visitors and can provide a variety of information, education, and recreation for visitors with a biophilic concept that creates rooms in buildings that have a natural impression and foster positive relationships between humans and nature. The purpose of this design is to meet the needs of educational facilities and economic drivers as well as recreational facilities, or can be called edu-tourism, which has workshop facilities, galleries, souvenir shops, cactus gardens, laboratories, and cafeterias. This facility is a public facility that targets the public, cactus farmers, and SMEs. The design location is in Lembang District, West Bandung Regency, West Java. which is an MSME area for cactus sales by local residents.